The Impact of Drinking Coffee in a Lying Position That Has an Impact on Increasing Pulse Rate - Fitri, Yuriska; Gandasari, Maharani Fatima; Salacup, Vince Louisse D. (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
The purpose of this study is to determine the impact of light doping due to drinking hot coffee and cold coffee in a lying position using an experimental method. With a sample of 16 sports students, namely 11 men and 5 women. The first step is to take a lying position and drink hot/cold coffee, then measure the pulse rate for 60 seconds, after that rest for 5 minutes, continue to drink hot/cold coffee, measure the pulse again for 30 seconds, rest again for 5 minutes, then drink hot/cold coffee followed by measuring the pulse again for 15 seconds. Then the normality test and the T test were carried out. The results of this study showed that there was a difference in pulse rate between hot coffee and cold coffee in the increase in pulse rate and it can be known that hot coffee increases the pulse rate the fastest compared to cold coffee.